Is Creative Commons a Panacea for Managing Digital Humanities Intellectual Property Rights? - Ding, Yi (Information Technology and Libraries, 2019)
Digital humanities is an academic field applying computational methods to explore topics and questions in the humanities field. Digital humanities projects, as a result, consist of a variety of creative works different from those in traditional humanities disciplines. Born to provide free, simple ways to grant permissions to creative works, Creative Commons (CC) licenses have become top options for many digital humanities scholars to handle intellectual property rights in the US. However, there are limitations of using CC licenses that are sometimes unknown by scholars and academic librarians. By analyzing case studies and influential lawsuits about intellectual property rights in the digital age, this article advocates for a critical perspective of copyright education and provides academic librarians with specific recommendations about advising digital humanities scholars to use CC licenses with four limitations in mind: 1) the pitfall of a free license; 2) the risk of irrevocability; 3) the ambiguity of NonCommercial and NonDerivative licenses; 4) the dilemma of ShareAlike and the open movement.